2004
DOI: 10.1111/j.1523-1755.2004.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and the risk of development of end-stage renal disease in a screened cohort

Abstract: We found that BMI was associated with an increased risk of the development of ESRD in men in the general population in Okinawa. The maintenance of optimal body weight may reduce the risk of ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
351
9
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 530 publications
(404 citation statements)
references
References 31 publications
26
351
9
9
Order By: Relevance
“…In contrast, no association was present between BMI and end-stage renal disease among participants of the Hypertension Detection Follow-up Study 5 . Among 100,753 members of a screened Japanese cohort, baseline BMI predicted future risk for end-stage renal disease in men but not women 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no association was present between BMI and end-stage renal disease among participants of the Hypertension Detection Follow-up Study 5 . Among 100,753 members of a screened Japanese cohort, baseline BMI predicted future risk for end-stage renal disease in men but not women 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, metabolic syndrome has been recently recognized as a major risk factor for progressive CKD. Iseki et al (29) reported that high body mass index was a risk for ESRD in Okinawa. In the study of the general population, Ninomiya et al (30) and Tanaka et al (31) reported that CKD incidence was significantly greater in individuals with metabolic syndrome, and the cumulative incidence of CKD increased in proportion to the increased number of metabolic syndrome risk factors, including hypertension, hypertriglyceridemia, low HDL cholesterol, and high blood glucose.…”
Section: Change In Policy For the Kidney Disease Screening Programmentioning
confidence: 99%
“…Higher BMI is associated with the presence 8 and development [9][10][11] of proteinuria in individuals without kidney disease. Furthermore, in numerous large population-based studies, higher BMI appears associated with the presence 8,12 and development of low estimated GFR 9,10,13 , with more rapid loss of estimated GFR over time, 14 and with the incidence of ESRD [15][16][17][18] . Elevated BMI levels, class II obesity and above, have been associated with more rapid progression of CKD in patients with pre-existing CKD 19 .…”
Section: Association Of Obesity With Ckd and Other Renal Complicationsmentioning
confidence: 99%